Valuing Flexibility as a Complex Option - Triantis, Alexander J.; Hodder, James E. (Journal of Finance, 1990)
This paper develops an approach for valuing flexible production systems using contingent claims pricing. Demand curves for our model's underlying assets (output products) may be downward sloping, in contrast with the standard option pricing assumption. Also, our marginal production(exercise) costs may be increasing. In addition, we allow for multiple products and a production capacity constraint. These elements of the model result in complex exercise decisions for the contingent claims which comprise the production system's value. We illustrate our approach by valuing a flexible system that produces two products which have profit margin functions with stochastic parameters.